Multi-Media Occurrence of Antibiotics and Antibiotic Resistance Genes in East Dongting Lake - Guo, Xiaochun; Song, Ranran; Lu, Shaoyong; Liu, Xiaohui; Chen, Jinming; Wan, Zhengfen; Bi, Bin (Frontiers in Environmental Science, 2022)
With the extensive use of antibiotics, antibiotics and their induced resistance genes (ARGs) have become a new type of pollutants widely distributed in a variety of environmental media. The contamination of antibiotic and ARGs occur in important living and agricultural regions has aroused wide concern worldwide, especially in lake basins. Dongting Lake basin is one of the important aquaculture and livestock areas in China, which is accompanied with a large amount of antibiotic use and discharge. However, the occurrence characteristics of antibiotics and ARGs in multi-environment medium are still unclear. In this study, surface water and sediment samples in East Dongting Lake were collected by season, antibiotics and ARGs were quantitatively analyzed, and the risk quotient (RQ) method was used to evaluated the ecological risk of antibiotics in surface water. (1) The concentration of antibiotics in surface water of East Dongiting Lake ranged from ND to 943.49 ng/L, with maximum average concentration of 20.92 ng/L in spring. The concentration of antibiotics in sediments ranged from ND to 177.43 ng/g, with maximum average concentration of 16.38 ng/g in fall. Ofloxacin (OFL) and sulfamethoxazole (SMX) were the main antibiotics pollutants in East Dongting Lake Basin. (2) sul1 and sul2 were the dominant ARGs in East Dongting Lake Basin. For spatial change, the total abundance of ARGs in upstream was higher than that in downstream. For seasonal change, the surface water and sediment were characterized by spring >summer >fall. (3) OFL and SMX might pose a significant high risk to aquatic organisms both in three seasons, and the ecological risk of antibiotics in East Dongting Lake are more significant at low temperatures than high. This study could provide important data information of the occurrence and concentration of antibiotics and ARGs in East Dongting Lake Basin.